2008
DOI: 10.2106/jbjs.g.00624
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Redisplacement of Distal Radial Fractures in Children

Abstract: Initial complete displacement and the degree of obliquity of the fracture line are the dominant factors affecting redisplacement. Our new radiographic index, the three-point index, should be used to predict redisplacement and assess the quality of the cast treatment of these fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
160
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(177 citation statements)
references
References 9 publications
10
160
2
5
Order By: Relevance
“…Previous studies on this fracture type have shown that initial displacement [8-11, 15, 16], failure to achieve a complete reduction [8,10,13,17], distal radius fracture with or without an ulna fracture [9,11,17,18], age [19], obliquity of the fracture [8,9] and poor casting [8] are significant risk factors for loss of reduction in this age group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on this fracture type have shown that initial displacement [8-11, 15, 16], failure to achieve a complete reduction [8,10,13,17], distal radius fracture with or without an ulna fracture [9,11,17,18], age [19], obliquity of the fracture [8,9] and poor casting [8] are significant risk factors for loss of reduction in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…According to Alemdaroglu et al [8], an incompletely reduced fracture is five times more likely to re-displace than those anatomically reduced. Roy et al [17] reported that fractures reduced to less than 50% apposition required re-manipulation more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations